A comparative study of social media networks among higher education students - Ali, Al Musawi; Daria, Bylieva; Mohamed, Osman; Abdulrahman, Ahmad; Asma, Al-Moqbali (Journal of Education and e-Learning Research, 2023)
This study aims to compare how students perceive and use social media networks (SMNs) in both Omani and Russian higher education institutions. An extensive literature survey was conducted through which the content of the questionnaire was compiled in English, validated for its content, clarity and accuracy by Russian and Omani reviewers and then translated. Data was collected from 837 undergraduate Russian and Omani students using online Google Forms. The results indicate a moderate level of SMNs use in both Higher Education Institution (HEIs) contexts with cross-platform mobile applications at the top of list of the SMNs used by both groups for social connections and multimedia sharing. The overall perceptions towards SMNs seem to be neutral among Russian and Omani students followed by positive perceptions. The study recommends that teachers in both countries provide ’attractive’ academic content through a social and multimedia design approach.